2008
DOI: 10.1086/589565
|View full text |Cite
|
Sign up to set email alerts
|

Polaris the Cepheid Returns: 4.5 Years of Monitoring from Ground and Space

Abstract: We present the analysis of 4.5 years of nearly continuous observations of the classical Cepheid Polaris, which comprise the most precise data available for this star. We have made spectroscopic measurements from ground and photometric measurements from the WIRE star tracker and the SMEI instrument on the Coriolis satellite. Measurements of the amplitude of the dominant oscillation (P ¼ 4 days), which go back more than a century, show a decrease from A V ¼ 120 to 30 mmag around the turn of the millennium. It ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 21 publications
(65 reference statements)
4
48
0
1
Order By: Relevance
“…The superimposed irregular behavior of Polaris resembles, in some ways, the Blazhko effect in RR Lyrae stars, as Evans et al (2004) and Bruntt et al (2008) have noted. Recently, a new theory of the Blazhko effect has been proposed (Stothers 2006) that may also explain Polaris.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The superimposed irregular behavior of Polaris resembles, in some ways, the Blazhko effect in RR Lyrae stars, as Evans et al (2004) and Bruntt et al (2008) have noted. Recently, a new theory of the Blazhko effect has been proposed (Stothers 2006) that may also explain Polaris.…”
Section: Introductionsupporting
confidence: 56%
“…However, their data reveal no trace of more than one mode being present, and the surprising change from falling to rising amplitude has occurred relatively smoothly. Similar objections have been raised by Bruntt et al (2008), who regarded the remarkable change of amplitude as being cyclic and possibly due to the beating of two very close periods. Although Arellano Ferro (1983) had already made essentially the same suggestion, he rejected it because the beat period would have to be of the order of a century long, which is unrealistic.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…These observations revealed that Polaris is not switching off and its pulsation amplitude started to increase after reaching a minimum around 2000. Weak excess variation in the low-frequency regime was tentatively connected to granulation patterns on the surface of the star ( [5]). …”
Section: Early Effortsmentioning
confidence: 98%
“…Interestingly, the first actual photometric mission was born from another mishap: the small optical star tracker camera on the otherwise unusable WIRE infrared space telescope was utilized to monitor bright stars. The well-known Cepheid Polaris (α UMi) was observed with it multiple times in 2004-5, complementing the more extended, but significantly lower-quality data set of the SMEI all-sky camera aboard the Coriolis satellite ( [5]). These observations revealed that Polaris is not switching off and its pulsation amplitude started to increase after reaching a minimum around 2000.…”
Section: Early Effortsmentioning
confidence: 99%